2018
DOI: 10.1093/alcalc/agx122
|View full text |Cite
|
Sign up to set email alerts
|

A Formative Evaluation of Two FASD Prevention Communication Strategies

Abstract: In this FASD prevention feasibility study, we found that FASD prevention messages, particularly paired with pregnancy test dispensers, placed in the women's restrooms of establishments that serve alcohol can effectively promote informed alcohol consumption decisions among women who are, or may become, pregnant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The authors suggested the small sample size, funding limitations that lead to change in counsellors in follow-up with possible rapport differences, and possible recollection errors in the TLFB due to the nature of self-reports, as limitations to their study. Driscoll et al (2018) evaluated the effectiveness, acceptability, and feasibility of FASD prevention messages in women's restrooms in a formative evaluation study. The authors placed health communication messages on pregnancy test dispensers or as posters in women's restrooms in establishments that served alcohol.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors suggested the small sample size, funding limitations that lead to change in counsellors in follow-up with possible rapport differences, and possible recollection errors in the TLFB due to the nature of self-reports, as limitations to their study. Driscoll et al (2018) evaluated the effectiveness, acceptability, and feasibility of FASD prevention messages in women's restrooms in a formative evaluation study. The authors placed health communication messages on pregnancy test dispensers or as posters in women's restrooms in establishments that served alcohol.…”
Section: Resultsmentioning
confidence: 99%
“…We found a huge variety in the study designs, including four randomised controlled trials (RCTs), a secondary data analysis, an observational comparative study, a case control study, a formative evaluation, a non-randomised pre-post intervention study, and an experimental randomised controlled trial. Seven out the 10 studies had follow-ups (Bazzo et al, 2015 ; Caley et al, 2010 ; Driscoll et al, 2018 ; Ingersoll et al, 2013 , 2018 ; Tenkku et al, 2011 ; Wilton et al, 2013 ), while Cil (Cil, 2017 ) compared administrative data over multiple years. Only one study investigated FASD incidence rates (Cil, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations